2012
DOI: 10.2134/agronj2011.0341
|View full text |Cite
|
Sign up to set email alerts
|

Rye–Corn Silage Double‐Cropping Reduces Corn Yield but Improves Environmental Impacts

Abstract: Recent proliferation of large dairies has prompted concern regarding environmental impacts of associated corn silage production and high-rate manure application. Our objectives were to compare environmental impacts and forage production of monocrop corn (Zea mays L.) silage and rye (Secale cereal L.)-corn silage double-crop systems with multiple corn planting dates and highrate manure application near Morris, MN. From 2007 to 2009, corn for silage was seeded into a silt loam as a monocrop in early and mid-May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
6
31
2
Order By: Relevance
“…Krueger et al (2012) indicated that corn yield decrease with RCC was likely a result of the rye-corn rotation affecting corn growth rather than RCC effects on soil supply of PAN, which could have been the case in our study and was confirmed by the relatively small differences in soil profile NO 3 -N between no-RCC and RCC. Corn grain yield decreased as RCC biomass increased.…”
Section: Corn Yield and Nitrogen Response Corn Yieldsupporting
confidence: 79%
See 1 more Smart Citation
“…Krueger et al (2012) indicated that corn yield decrease with RCC was likely a result of the rye-corn rotation affecting corn growth rather than RCC effects on soil supply of PAN, which could have been the case in our study and was confirmed by the relatively small differences in soil profile NO 3 -N between no-RCC and RCC. Corn grain yield decreased as RCC biomass increased.…”
Section: Corn Yield and Nitrogen Response Corn Yieldsupporting
confidence: 79%
“…However, research has found differing annual crop yield responses with RCC. Corn grain and silage yield decreases have been reported with use of RCC (Raimbault et al, 1990;Kessavalou and Walters, 1997;Thelen and Leep, 2002;Singer and Kohler, 2005;McDonald et al, 2008;Kramberger et al, 2009;Salmerón et al, 2011;Krueger et al, 2012;Reese et al, 2014). A 15% corn yield increase was observed in 2 out of 3 yr in a study conducted on sandy soils in Wisconsin with no N application to the RCC and with low RCC biomass production .…”
mentioning
confidence: 99%
“…Results confirmed that, when planted after corn silage harvest, a rye cover crop can provide environmental benefits (Krueger et al 2010;Krueger et al 2011;Krueger et al 2012) without impacting subsequent corn yield even in a cold climate (Krueger et al 2011). Rye/corn silage cropping systems prevented soil NO 3 -N accumulation and reduced soil solution NO 3 -N concentration compared with corn silage alone, while also increasing ground cover and soil organic C (SOC) relative to corn silage without a cover crop (Krueger et al 2010;Krueger et al 2011;Krueger et al 2012). However, when rye was allowed to grow until it could be harvested for forage (i.e., forage double-cropping), significant reductions in subsequent corn silage yield occurred, primarily resulting from soil moisture and NO 3 -N depletion that increased with greater rye growth.…”
mentioning
confidence: 67%
“…With its short growing season, corn silage provides little vegetative cover much of the year (Krueger et al 2012), which leaves the soil prone to erosion by wind and water Abstract: Increased corn (Zea mays L.) silage and manure production accompanying the proliferation of large dairies has prompted concern regarding their environmental impacts. The objectives of this on-farm, field-scale study were (1) to quantify environmental impacts, e.g., soil chemical properties and offsite nutrient transport, of corn silage production with dairy manure application on artificially drained soils and (2) to assess the environmental benefits of and agronomic constraints on the adoption of winter rye (Secale cereale L.) cover cropping by a large dairy in west central Minnesota.…”
mentioning
confidence: 99%
See 1 more Smart Citation